PENGARUH PENGAWASAN, KOMPETENSI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. LUNADORII UTAMA INDONESIA - Eka Novita Sari; Hendra Nazmi; Putri Balqis (Universitas Methodist Indonesia, 2020)
The purpose of this study was to examine the effect of supervisory work, competence and satisfaction on employee performance at PT. Lunadorii Utama Indonesia. The population in this study were 126 respondents, and the sample was 96 people. The sampling technique used was simple random sampling. The results showed that simultaneously supervision, competence, and job satisfaction had a positive and significant effect on employee performance at PT. Lunadorii Utama Indonesia. The coefficient of determination test results obtained Adjusted R Square value of 0.378, this means 37.8% of the variables tied to employee performance can be carried out by the independent variables, while the remaining 62.2% is explained by other variables not examined in this study, such as career development, promotion, compensation, and work environment.